Effects of resistance exercise intensities and blood flow supply on regulators of myogenesis in human skeletal muscle - Popov, D.; Furalyov, V.; Kravchenko, I.; Miller, T.; Bachinin, A.; Kurochkina, N.; Moroz, A.; Vinogradova, O. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Choosing an optimal contractile activity protocol associated with resistance exercise for improving an increase in muscle mass is an important task for a rehabilitation medicine and a sporting activities. The aims of the present study were to compare an expression of myogenesis regulators in human skeletal muscle 1) after moderate-intensity resistance exercise with (MI) and without (with blood flow restriction) relaxation (MIWR) and 2) after high-intensity (HI) and MI resistance exercise. Methods: Seven men adapted to strength training performed three resistance exercise sessions three times on separate days in a randomized order: 1) MIWR (8 x 12 knee extensions without relaxation, 50% 1RM, 7 min recovery), 2) MI (8 x 12 knee extensions, 50% 1RM, 7 min recovery), 3) HI (8 x 12 knee extensions, 75% 1RM, 7 min recovery). The duration of muscle activity during exercise in different sessions was equalized. The venous blood samples were taken before, during and 15 min after exercise sessions for determination of lactate, glucose, cortisol (C), testosterone (T), growth hormone (GH), insulin (I) and insulin-like growth factor 1 (IGF-1) concentrations. The vastus lateralis muscle biopsies were collected before, 40 min, 5 and 22 h after the exercise session and analyzed by qPCR for mRNA expression of IGF-1EA, IGF-1EC (MGF), Myostatin, MyoD, p21 and MyHC-2x. Results: The lactate concentration after MIWR was 7.9(6.6-8.7) mM that was significantly higher (p<0.05) than after both HI: 5.8(5.0-7.3) mM and MI: 2.6(2.5-4.3) mM sessions. The concentrations of glucose, I, IGF-1 after exercise did not change and did not differ between sessions. The concentrations of C after HI and after MIWR were higher (p<0.05) than after MI. The decrease (p<0.05) of T concentration was found after MIWR only. MIWR led to a decrease (p<0.05) of Myostatin mRNA abundance at 40 min and 22 h of recovery: 0.35(0.23-0.78)- and 0.2(0.01-0.5)-fold relative to initial level, respectively. Myostatin mRNA abundance decreased (p<0.05) 22 h after HI: 0.1 (0.08-0.23)-fold relative to initial level, and did not change during recovery after MI session. Difference (p=0.06) of myostatin mRNA abundance was found between HI and MI at 5 h of recovery: 0.6(0.16-1.27)- and 1.3(0.28-6.6)-fold relative to initial level, respectively. MyHC-2x mRNA abundance increased at 5 h of recovery after MIWR: 2.75(0.88-16.7)-fold relative to initial level, and did not change during recovery after HI and MIWR. The expression of IGF-IEA, IGF-IEC (MGF), MyoD and p21 mRNA did not change during recovery and did not differ between exercise sessions as well. Discussion: The current study demonstrated that in skeletal muscle of men adapted to strength training 1) the decrease of myostatin mRNA abundance after MIWR was comparable with the decrease of myostatin mRNA abundance after HI. 2) Myostatin mRNA expression during recovery was associated with intensity of resistance exercise, if it was performed without blood flow restriction. The work is supported by RFBR grant # 12-04-01668-à.